The Construction of Moderate Islamic Discourse and the Filmmaker’s Political Bias in Ayat- ayat Cinta 2 - Herza, Herza; Murtada, Muhammad Muflih; Saputra, Putra Pratama (P3M Politeknik Negeri Media Kreatif, 2023)
This paper aims to analyze how Islamic discourse is constructed in the film Ayat-ayat Cinta (AAC) 2, analyze the political position of the filmmaker in the Palestinian-Israeli conflict, and analyze the hyperreality dimension in the film AAC 2 according to Jean Baudrillard's thoughts. Norman Fairclough's critical discourse analysis was used as a theoretical perspective as well as a method in this paper. This research approach was qualitative with data sources from film text as primary data, as well as journal articles, books, media articles, and film-related social media posts, as secondary data. The results of the analysis revealed that through the roles played by the characters Fahri, Hulya, Sabhina (Aisha), the filmmaker has constructed a moderate Islamic discourse that is so dominant throughout the film. Through several film scenes, the filmmaker also explicitly showed his political alignments with the Palestinian state and builds an image of anti-human values towards the Israeli army. The representation of the religious life of Islamic figures, as well as scenes about Palestinian women (supporters) and Israeli soldiers in this film were included in Jean Baudrillard's hyperreality